A new holistic conceptual framework for sustainability oriented hospitality innovation with triple bottom line perspective. (21st October 2019) - Ozturkoglu, Yücel; Sari, Ferika Ozer; Saygili, Ebru
Abstract : Purpose: The purpose of this study is to determine the dimensions for "sustainability-oriented hospitality service innovation (SOHSI)" in the context of food and beverage (F&B) industry. For this to be done, the relationship between service innovation dimensions and the triple bottom line (TBL) dimensions (including social, environmental and economic aspects of sustainability) is investigated. Design/methodology/approach: In this study, primarily a detailed literature review was carried out to specify the dimensions of service innovation in hospitality industry and sustainability as well. Then, fuzzy decision-making trial and evaluation laboratory (DEMATEL), one of the multi-criteria decision-making (MCDM) methods, was used to reveal the causal relationship within these dimensions. Findings: A framework is presented to help F&B organizations make their innovative services more sustainable. F&B servicing companies should focus especially on "environmental entrepreneurship, " "interior design" and "brand management" dimensions to get benefit underway to gain competitive advantage. Originality/value: In hospitality industry where competition is increasing every day, it is necessary to create brand-new services or offer renowned services via diversified ways, to step forward from competitors. In this regard, it is important for companies to ensure that every innovative service should be sustainable. Until now, researchers have mostly studied environmental dimension of sustainable service innovation. However, there are no studies evaluating sustainability concept with the TBL approach. Therefore, this study contributes to the field of sustainability in hospitality service innovation. Abstract : 论新一体化理论模型：以三重底线为视角的可持续性导向的酒店服务创新 抽象 研究目的: 本论文旨在定义 "可持续性导向的酒店服务创新"（SOHSI）在餐饮业的维度。以达到此目的, 本论文研究了服务创新维度和三重底线维度（包括可持续性的社会、环境、和经济三方面）。 研究设计/方法/途径: 本论文主要采用文献综述的方式来定义酒店服务业和可持续领域中的服务创新维度。此外, 本论文使用Fuzzy DEMATEL （决策实验室分析法）, 一种多准测决策法（MCDM）, 以探究为度之间的因果关系。 研究结果: 本论文提出了一个理论模型, 以帮助餐饮企业使得他们的创新服务更加可持续化。餐饮服务企业尤其应该专注"环境企业家精神"、"室内设计"、"品牌管理"等维度, 以获得市场竞争力。企业应该确保每个创新服务都应该是可持续性的。至今为止, 研究者们大多数专注于可持续服务创新中的环境维度。然而, 尚未有研究采用三重底线分析法来探究可持续性这个概念。因此, 本论文对酒店服务创新中的可持续性领域做出贡献。 关键字: 关键词 服务创新、可持续性、酒店服务、餐饮、三重底线 论文类型: 理论型论文